Comparative Evaluation of The Efficacy of Topical Hyaluronic Acid ( 0.2%) and Topical Triamcinolone Acetonide( 0.1%) in The Treatment of Recurrent Aphthous Stomatitis - Nzhad Mustafa, Bero; Fakhree Alzubaidee, Ali (Diyala Journal of Medicine, 2020)
Background: Recurrent aphthous ulcers are the most common oral lesion. They are classified into minor, major, and herpetiform ulcers. More than 85% of recurrent aphthous stomatitis presents as a minor ulcer. Hyaluronic acid is a biomaterial and it is a major carbohydrate component that can be found in many tissues and recently introduced as an alternative approach to enhance wound healing. Triamcinolone acetonide is a synthetic corticosteroid and it has two forms for topical use cream (0.1%) and ointment (0.1%). Objective: To make a comparison between the effectiveness of hyaluronic acid (0.2%) and triamcinolone acetonide (0.1) in the management of recurrent aphthous ulcer. Patients and Methods: We recruited eighty patients who had a history of recurrent aphthous stomatitis and when presented with current oral ulcer and randomly divided into two groups, one group received hyaluronic acid, and the other group received triamcinolone acetonide. The instruction was given to all patients to apply the agent to the aphthous ulcer 4 times per day for 6 days (day 0 to day 6). The severity of pain was assessed by using VAS and the change of the ulcer surface area measured. Results: Eighty patients with aphthous ulcers have participated in the study, 43 were treated with hyaluronic acid, 37 were treated with triamcinolone acetonide. There was a significant difference between the two groups regarding ulcer surface and after three and six days, the diameter of the ulcer in the hyaluronic acid group was significantly reduced in comparison with those of the triamcinolone acetonide group (p < 0.001). Regarding VAS for pain, there was a significant difference after three and six days, hyaluronic acid group had significantly less VAS than those of the triamcinolone acetonide group (p = 0.004 and p < 0.001 respectively). Conclusion: Hyaluronic acid is more effective than triamcinolone acetonide when used in the treatment of recurrent oral ulcers in reducing pain and surface area of the ulcer.